Optimisasi Operasi Pemboran Di Basin Afrika Utara - Aly Rasyid; Nugroho Marsiyanto (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Drilling optimization objective was to reduce costs, improve wellbore conditions and integrity for increasingly challenging reservoirs while establishing maximum safety performance and environmental custodianship. Even though the final result of a drilling operation is easily observed, what almost always goes unnoticed is the complexity of the issues involved in the planning and execution of a drilling operation and the number of topics involved in such a process. In this paper, as case study of the exploration drilling in Hamada region, North Africa has been evaluated. Over the period of 2006 to 2011, continued drilling improvement was achieved. Key elements in the optimization included focus on management drilling team structure, engineering well planning, improvements on managing drilling operations such as on site safety management practices, and also post drill analysis to implement lesson learn for the next well to be drilled. As the result, while drilling 26 wells during the 2006 until 2011, drilling days were successfully reduced from 87 days (first well) to the average 40 days, and very good safety record performance.